Letter on an Ostracon From the Settlement of Vyshesteblievskaya-3 - Kashaev, Sergey; Pavlichenko, Natalia (Hyperboreus, 2015)
In 2013 at the settlement of Vyshesteblievskaya-3 was found a fragment (broken on the left) of the wall of a Mediterranean amphora with an inscription: – [Δημητρ?]ίη Ἀπολλᾶι χαί/[ρειν. - - -]ΟΥΡΑΙ ὅρωι μὴ ἀποπεράσηι. ῾Ως μὴ ἀποπερά/[σηι. ῾Ω]ς μὴ ἀποπεράσηι [- - -?]. (“Demetria (?) wishes Apollas well. [- - -]OURAI (scil. the plot) with a safeguard stone so that he cannot sell it! So that he cannot sell it [- - -?]!”). The ostracon was retrieved from a turf layer (square А, Б-80; area 40) in the area where a structure arbitrarily called the ‘Ditch’ was excavated at the level of the virgin soil. The type of letter allows us to date it only broadly to the second half of the fourth century BC. The ostracon published here is thus one of the rare pieces of written evidence of the existence of a system of ancient land division on the Taman Peninsula as also conﬁrmed by archaeological excavations and surveys of recent years.